Recent trends in PEM fuel cell-powered hybrid systems: Investigation of application areas, design architectures and energy management approaches - Erdinc, O.; Uzunoglu, M. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Recently, the renewable energy issue is becoming significant due to increasing power demand, instability of the rising oil prices and environmental problems. Among the various renewable energy sources, fuel cell (FC) technology has received considerable attention as an alternative to the conventional power units due to its higher efficiency, clean operation and cost-effective supply of power demanded by the consumers. Particularly, proton exchange membrane (PEM) FC technology plays a leading role for many applications when comparing with other competitive types of FCs. PEMFCs have recently passed the test or demonstration phase and have partially reached the commercialization stage due to the impressive worldwide research effort. Besides, providing a hybrid system by integration of PEMFC with an auxiliary power source may provide better results considering the issues of performance and component durability. This paper presents a comprehensive review of the recent trends in PEMFC powered hybrid systems including a detailed explanation of application areas and design architectures with different power electronics interfaces as well as the energy management methods utilized in the daily life and taking part in the literature. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: PEM fuel cell; Hybrid system; Application area; Design architecture; Power electronics interface; Energy management; DC-DC CONVERTER; CONTROL STRATEGY; FUZZY-LOGIC; ROBUST-CONTROL; GENERATION SYSTEM; ADAPTIVE-CONTROL; HYDROGEN; SIMULATION; MULTIPLE; OPTIMIZATION; Science & Technology - Other Topics; Energy & Fuels